Analisis Implementasi Model ADDIE dalam Perencanaan dan Pengembangan Pembelajaran Inovatif - Rachmad Rizal Yulianto (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Effective learning planning requires teachers to design learning processes that are systematic, creative, and aligned with students’ needs. The ADDIE model is one of the most systematic and flexible instructional design frameworks, used to assist educators in planning and evaluating learning processes effectively. This study aims to analyze the application of the ADDIE model in planning and designing innovative learning through a literature review approach. The review was conducted by examining various scholarly sources, including journals, books, and previous research related to instructional design development. The analysis revealed that the ADDIE model enhances learning effectiveness by providing clear guidance from needs identification, strategy design, and media development to learning evaluation. Its implementation is also relevant to 21st-century learning characteristics, emphasizing creativity, collaboration, and the integration of digital technology. However, challenges such as limited time, inadequate resources, and teachers’ pedagogical competence remain obstacles in its practical application. Therefore, continuous professional training and supportive educational policies are essential to promote innovative learning. The ADDIE model serves as a strategic approach to creating adaptive, reflective, and learner-centered educational practices.   Keywords: ADDIE Model, Instructional Design, Innovation, Education, Literature Review